116k views
2 votes
Solve 3(x+1)=7(x-2)-3

User Srbhkmr
by
4.6k points

2 Answers

3 votes

Answer:

x = 5

Explanation:


3(x+1)=7(x-2)-3\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(3)(x)+(3)(1)=(7)(x)+(7)(-2)-3\\\\3x+3=7x-14-3\qquad\text{combine like terms}\\\\3x+3=7x+(-14-3)\\\\3x+3=7x-17\qquad\text{subtract 3 from both sides}\\\\3x+3-3=7x-17-3\\\\3x=7x-20\qquad\text{subtract 7x from both sides}\\\\3x-7x=7x-7x-20\\\\-4x=-20\qquad\text{divide both sides by (-4)}\\\\(-4x)/(-4)=(-20)/(-4)\\\\x=5

User Tommymaynard
by
5.7k points
3 votes

Answer:

x = 5

Explanation:

To solve this, we just have to the multiplication and do the simplification (adding up the similar terms) afterwards:

3(x+1)=7(x-2)-3 becomes...

3x + 3 = 7x - 14 - 3

3x + 3 = 7x -17

Then we move all x's on one side and all plain numbers on the other side, we'll move the x's to the right since there's a bigger value there, and will move the plain numbers on the left side, by subtracting 3x and by adding 17 on both sides

3x + 3 - 3x + 17 = 7x -17 + 17 - 3x

20 = 4x

If we isolate x alone we have:

20/4 = x or x = 5

User Bruno Zamengo
by
5.4k points